Gender and subject domain differences in metacognitive awareness among pre-service teachers - Jikamshi, Mahmud Haruna; Abdullah, Maria Chong; Roslan, Samsilah; Ismail, Habsah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study examined the gender and subject domain differences in the dimensions of metacognitive awareness of pre-service teachers. In this quantitative study, a total of 418 pre-service teachers participated in the study comprising of, 215 males and 203 females, studying in colleges of education in Northern Nigeria. An independent sample t-test was employed for the data analysis in this study. The result shows a significant gender difference in the dimension of cognition of knowledge, with females having the higher means score. However, the result indicated no significant gender difference in the dimension of regulation of knowledge. With regards to subject’s domain, the finding revealed a significant difference between art and science, with arts students having higher means score compared to science students in both dimensions of cognition of knowledge, and regulation of knowledge. The study concluded that, females tend to have high metacognitive awareness, and art students tend to have higher metacognitive awareness. Theoretical and practical implications of the study, as well as recommendations for future research, have been presented as well.